Discrete Functions of Nuclear Receptor Rev-erbα Couple Metabolism to the Clock - Zhang, Yuxiang (Science, 2015)
Circadian and metabolic physiology are intricately intertwined, as illustrated by Rev-erbα, a transcription factor (TF) that functions both as a core repressive component of the cell autonomous clock and as a regulator of metabolic genes. Here we show that Rev-erbα modulates the clock and metabolism by different genomic mechanisms. Clock control requires Rev-erbα to bind directly to the genome at its cognate sites, where it competes with activating ROR TFs. By contrast, Rev-erbα regulates metabolic genes primarily by recruiting the HDAC3 corepressor to sites to which it is tethered by cell type-specific transcription factors. Thus, direct competition between Rev-erbα and ROR TFs provides a universal mechanism for self-sustained control of molecular clock across all tissues, whereas Rev-erbα utilizes lineage-determining factors to convey a tissue-specific epigenomic rhythm that regulates metabolism tailored to the specific need of that tissue.